Diagnostic accuracy of minimally invasive markers for detection of airway eosinophilia in asthma: a systematic review and meta-analysis. Issue 4 (April 2015) - Korevaar, Daniël A; Westerhof, Guus A; Wang, Junfeng; Cohen, Jérémie F; Spijker, René; Sterk, Peter J; Bel, Elisabeth H; Bossuyt, Patrick M M
Summary Background Eosinophilic airway inflammation is associated with increased corticosteroid responsiveness in asthma, but direct airway sampling methods are invasive or laborious. Minimally invasive markers for airway eosinophilia could present an alternative method, but estimates of their accuracy vary. Methods We did a systematic review and searched Medline, Embase, and PubMed for studies assessing the diagnostic accuracy of markers against a reference standard of induced sputum, bronchoalveolar lavage, or endobronchial biopsy in patients with asthma or suspected asthma (for inception to Aug 1, 2014). Unpublished results were obtained by contacting authors of studies that did not report on diagnostic accuracy, but had data from which estimates could be calculated. We assessed risk of bias with QUADAS-2. We used meta-analysis to produce summary estimates of accuracy. Findings We included 32 studies: 24 in adults and eight in children. Of these, 26 (81%) showed risk of bias in at least one domain. In adults, three markers had extensively been investigated: fraction of exhaled nitric oxide (FeNO) (17 studies; 3216 patients; summary area under the receiver operator curve [AUC] 0·75 [95% CI 0·72–0·78]); blood eosinophils (14 studies; 2405 patients; 0·78 [0·74–0·82]); total IgE (seven studies; 942 patients; 0·65 [0·61–0·69]). In children, only FeNO (six studies; 349 patients; summary AUC 0·81 [0·72–0·89]) and blood eosinophils (three studies; 192 patients; 0·78 [0·71–0·85]) had been investigated in more than one study. Induced sputum was most frequently used as the reference standard. Summary estimates of sensitivity and specificity in detecting sputum eosinophils of 3% or more in adults were: 0·66 (0·57–0·75) and 0·76 (0·65–0·85) for FeNO; 0·71 (0·65–0·76) and 0·77 (0·70–0·83) for blood eosinophils; and 0·64 (0·42–0·81) and 0·71 (0·42–0·89) for IgE. Interpretation FeNO, blood eosinophils, and IgE have moderate diagnostic accuracy. Their use as a single surrogate marker for airway eosinophilia in patients with asthma will lead to a substantial number of false positives or false negatives. Funding None.